Fabrication of chemically stable hydrogen- and niobium-codoped ZnO transparent conductive films. Issue 22 (24th April 2019) - Han, Bing; Song, Jianmin; Li, Junjie; Guo, Yajuan; Dai, Binting; Meng, Xudong; Song, Weiye; Yang, Fu; Wang, Yanfeng
Abstract : H- and Nb-doped ZnO (HNZO) thin films were fabricated on glass substrates with radio frequency magnetron sputtering. Abstract : H- and Nb-doped ZnO (HNZO) thin films were fabricated on glass substrates with radio frequency magnetron sputtering. The effect of the flow rate of H2 has been investigated by analyzing the structural, optical, and electrical properties. The incorporation of H during the deposition of Nb-incorporated ZnO films significantly improved their crystallinity, conductivity, and transmittance. The crystallites of the HNZO films were preferentially oriented in the c -axis direction; the films possess high transmittance (approximately 85%) in the visible and near-infrared regions (400 to 1400 nm). The lowest room-temperature resistivity of the HNZO films was measured as 1.28 × 10 −3 Ω cm. Such optical and electrical properties along with the remarkable chemical stability of the HNZO films make them a promising candidate for applications in solar cells.